PHYSICOCHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF RED GUAVA (Psidium guajava L.) JUICE INSTANT DRINK POW- DER PRODUCED USING FOAM-MAT DRYING METHOD - Sandi Darniadi; Iyan Sofyan; Dede Z. Arief (Pusbindiklat - LIPI, 2011)
Powder product as instant drink from red guava (Psidium guajava L.) juice is more practicable to increase economic value. The objective of the research was to investigate physicochemical and organoleptic characteristics of red guava juice instant drink powder produced using foam-mat drying method. The results showed that red guava juice instant drink powder produced using foam-mat drying method had high yield with solubility was low, the brightness was high, the level of redness was high, the level of yellowish was low, sugar was high, and sensory properties were accepted by panelist.